The impact of coaching and mentoring of experienced teachers on successfulness of fresh teachers - Bijandi, Mohammad Sadegh; Hassan, Aminuddian; Sulaiman, Tajularipin (Faculty of Educational Studies, Universiti Putra Malaysia, 2009)
A lot of fresh teachers in schools don't have the abilities and expertise for doing their jobs professionally. This lack of abilities without pay attention to the roots of them must be improved and solved. Sometimes the Education systems don't follow their rules for employing teachers, so some persons who don't have the requirements for being teachers are accepted as teachers. Sometimes the education methods are not up-to date, complete and enough for training teachers in universities. Therefore, the desired outcomes of system are not fulfilled not only by teachers but also by parents and students. For solving these troubles, the experienced teachers in each school are the best choice to guide and help fresh teachers. With encouragement among fresh and experienced teachers, they will reach to qualitative and quantitative promotion, improving function and job satisfaction. The author believes that the problems of fresh teachers is the present and future problem in education system so in this essay a strategic plan will be presented for having a good and successful method for fresh teachers to achieve the schools' and teachers' aims and objectives by obtaining help from the experienced teachers.